Widening Access To Secondary Education In Africa: What Lessons Could Africa Learn From East And Southeast Asian Countries? - Ohba, Asayo (Penerbit Universiti Sains Malaysia, 2012)
As many countries in sub-Saharan Africa meet universal primary education, widening access to secondary education is becoming an increasingly urgent issue for governments to address. How can African countries achieve mass secondary education available for all? This paper reviews experiences in East and Southeast Asian countries in widening access to secondary education and draws lessons that might be applicable to countries in sub-Saharan Africa. Firstly, the paper looks at macro factors that contributed substantially to the widening of access to secondary education in East and Southeast Asian countries. It then scrutinises micro factors to evaluate how it actually had influences on expanding access.